The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0101-60832002000600002
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: do men and women suffer from the same disease?

Abstract: This article reviews the literature on normal brain development and behavioural development in men and women as well as on aetiological risk factors for schizophrenia, such as pre-, peri-and postnatal complications.The male-female comparisons of age and type of onset, symptomatology, course and outcome were based on a population-based sample of 232 first illness episodes -the ABC Schizophrenia Study sample. The probands were assessed using the IRAOS interview and other instruments retrospectively at first admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 126 publications
(88 reference statements)
2
18
0
Order By: Relevance
“…The lower prolactin levels in male participants might partially explain their lower ASEX scores and rates of sexual dysfunction. In concordance the research of Häfner (2002) , our study also recorded a higher rate of marriage and partnership among female participants compared with the male participants.…”
Section: Discussionsupporting
confidence: 89%
“…The lower prolactin levels in male participants might partially explain their lower ASEX scores and rates of sexual dysfunction. In concordance the research of Häfner (2002) , our study also recorded a higher rate of marriage and partnership among female participants compared with the male participants.…”
Section: Discussionsupporting
confidence: 89%
“…In relation to onset of illness, in the ABC first-episode sample with a broad definition of schizophrenia, Häfner [ 51 ], showed that the disorder manifests itself clearly later in women than men, from the first sign of the illness. Women's mean age at first symptom was 25.4 years, 2.9 years higher than men's age.…”
Section: Resultsmentioning
confidence: 99%
“…These two aspects – sex specificity and anomalous asymmetry – are both consistent with, and provide support for, the hypothesis that these structural anomalies are byproducts of an early developmental disturbance. It is a clinical truism that schizophrenia often presents quite differently in men and women, with some even questioning whether they share the same illness (Häfner, 2002). Likewise, the idea that schizophrenia is characterized by a disruption of the normal emergent pattern of cerebral asymmetry, which preferentially alters left hemisphere development (especially of the temporal lobes) and leads to more prominent left hemisphere dysfunction, is a long-standing one for which there is substantial evidence (Crow et al, 1989).…”
Section: Discussionmentioning
confidence: 99%